EXPLORING THE TRACES OF RACISM IN THE MOVIE THE HATE U GIVE - Nabeela Gul; Huma Khan; Fariah Bilal; Maqsood Ur Rehman; Muhammad Azaz Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
This research is the study about racism that appears in THE HATE U GIVE movie, directed by George Tillman Jr. This movie tells about Racism and Discrimination which is done by the white people a majority towards the black people as minority. This research paper is aimed to analyses the racism that reflected in THE HATE U GIVE movie. This type of research is qualitative descriptive while the technique of analyzing data is descriptive technique. In this research the researcher use Van Dijk model of US and THEM. After the data analysis, the researcher finds that there are indicators of racism in THE HATE U GIVE movie and describe how racism happened in the movie based on Van Dijk model of US and THEM. This research has several conclusions 1) Unfair treatment and discrimination experienced by the black people 2) The black people always blamed just because they are black and considered as bad and evil in society.